Habermas og Nietzsche - Andersen, Vagn (Religionsvidenskabeligt Tidsskrift, 1985)
The subject of this article is a confrontation between the thought of Jürgen Habermas and the perspectivistic epistemology of Friedrich Nietzsche. It is held that for a post-ontological philosophy, Nietzsche’s theory of knowledge his programmatic view that every “truth” it just an “interpretation” is in a certain sense invincible. Habermas does not fundamentally overcome this situation. Nevertheless Habermas has been able to develop a linguistic theory of rationality, which combining inspiration from the philosophical hermeneutics of Hans-Georg Gadamer and the speech-act-philosophy of John L. Austin and John R. Searle makes the nihilistic consequences, which Nietzsche draws from his “theory of interpretations”, pointless. At the same time the theory of Habermas overcomes the paradoxical self-destructing position, in which the old “School of Frankfurt” ended. Following some crucial stages in the philosophical development of Habermas, it is shown how he has come to his present point of view.